Aspect Of Financial Policy In An Open Developing Economy: The Malaysian Example - Hussin, Awang Adek B. (1984)
The study deals with several key aspects of financial policy in the context of the small-open-developing economy of Malaysia, in which a well-developed capital market is absent. Given the structure of the economy, some interesting issues pertaining to the scope and conduct of monetary policy, the extent and channels of transmission of foreign disturbances, and the choice of an exchange rate system are investigated. A major focus of the study is on the development of the analytical model of the economy where the emphasis is placed on the financial sector.